2019
DOI: 10.3390/ijerph16132429
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the Sustainable Development Goals: A Mixed Methods Study of Health-Related Water, Sanitation, and Hygiene (WASH) for Indigenous Shawi in the Peruvian Amazon

Abstract: Sustainable Development Goal 6 (SDG-6) addresses poor water quality, inadequate sanitation, and improper hygiene, all of which negatively impact health and disproportionately impact Indigenous Peoples’ health. Understanding and responding to local contexts is critical to effectively improve water, sanitation, and hygiene (WASH); however, in-depth understanding of local knowledge, practices, and perceptions are often overlooked. As such, this study described the knowledge, practices, and perceptions of WASH hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The high load of total and fecal coliforms found in the water sources of the community, other than masato, may be due to contamination of the main source of domestic water, the Armanayacu River. River water contamination stems from multiple factors, including open defecation by the river despite the availability of a few latrines in the community (Torres-Slimming et al 2019). Additionally, wild and domestic animals (e.g., cattle and pigs) also roam river banks, adding to potential sources of water contamination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high load of total and fecal coliforms found in the water sources of the community, other than masato, may be due to contamination of the main source of domestic water, the Armanayacu River. River water contamination stems from multiple factors, including open defecation by the river despite the availability of a few latrines in the community (Torres-Slimming et al 2019). Additionally, wild and domestic animals (e.g., cattle and pigs) also roam river banks, adding to potential sources of water contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all masato samples were provided by the head of the households, and handwashing and serving practices may have varied by household. Shawi have reported that they wash their hands before serving masato, although use of soap is not a common practice (Torres-Slimming et al 2019). Future studies could analyze coliform load per preparation method, days of fermentation, and the effect of unwashed hands on coliform presence.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Families are located near the wife's parents, following a matrilocal social organization. Shawi relationships with the environment, and water in particular, continue to be grounded in spiritual cosmology, kinship, and reciprocity [58]. Shawi livelihoods tend to be gendered: slash and burn agriculture is practiced by both men and women, whereas hunting and small scale fishing are typically only conducted by men [59,60].…”
Section: Community Profile: Loreto Region Peruvian Amazonmentioning
confidence: 99%
“…Transect walking path activities involved "walking with participants along a path to explore Shawi connections to their environment, their sense of place, and their relationships with water" [58] as it relates to climate change and environmental changes [67,68]. These dynamic conversations were audio recorded and photographed with permission and informed consent.…”
Section: Qualitative Data Collectionmentioning
confidence: 99%